Pengaruh Pembelajaran STEAM Terhadap Peningkatan Pemahaman Lingkungan Geografis Pada Anak Usia 5-6 Tahun - Atikah Isnaini Fitri Sofian; Nur Ika Sari Rakhmawati (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
STEAM learning is one of the appropriate learning and support the demands of the 21st century. This learning is a contextual learning where children are invited to understand and observe the events that occur near them. Children need to be given the opportunity to relate to the surrounding environment which can be done through learning about the geographical environment. This study aims to determine the difference in the ability to understand the geographical environment between groups that use STEAM Learning with groups that do not use STEAM learning. The method used is quantitative with the type of research quasi experimental design that uses non-equivalent control group design. The samples used were 24 children with an age range of 5-6 years in kindergarten located in Kembangbahu District, Lamongan regency. This study used 2 kindergartens in Kembangbahu subdistrict, Lamongan regency consisting of an experimental group and a control group. The results showed that there is an influence of STEAM learning to understand the geographical environment of children aged 5-6 years as evidenced by the results of hypothesis testing post-test data obtained the value of asymmp. sig. (2-tailed) 0.004 is smaller than 0.05. In addition, there was an increase in the average value of understanding the geographical environment from pre-test to post-test after being given treatment in the form of STEAM learning in the experimental class.